Self-powered portable solar tracking system - Li, Jiwei (2016)
Solar energy as one of the most promising renewable power source has been further developed and wildly applied in Singapore. The sun light condition is required for installation purpose. In this project, a portable device was designed and produced to monitor the sun path at the particular locations. Cameras and micro-controllers are used to compose the solar tracker. As the result, the device was built to capture images of the sky. With the help of MatLab, the location of the sun can be analyzed from the images and present as the incident angle with the observing position as the reference point. By building of the portable solar tracking system, a series of data such as peak sun hours and incident angles can be provided and applied in many related industries like solar power installation and architectural designs.